A rapid, cost-effective method for counting human embryonic stem cell numbers as clumps. (July 2009) - Prowse, Andrew B.J.; Wolvetang, Ernst J.; Gray, Peter P.
Enumeration of human embryonic stem cell (hESC) numbers through single cell digestion can be time consuming especially in high-throughput or multi-factorial analysis containing 50+ samples. We have developed a reproducible, cost-effective method of counting hESCs in clumps circumventing the need to manually dissociate each sample to single cells. The method is based on the DNA binding capacity of propidium iodide (PI) and subsequent fluorescent signal detection. Standard curves generated for cell numbers versus PI fluorescence as single cells or clumps showed an almost identical relationship in the lines of best fit. The reproducibility of the assay was first demonstrated by seeding hESC clumps at specific cell densities ranging 0.05–2 × 10 5 cells/well and then secondly by using the assay to count cell numbers after different growth conditions. Validation tests showed that consistent seeding densities are important in maintaining undifferentiated hESC culture and that the assay can be used to estimate relative cell numbers and growth curves with high accuracy.